(untitled) (LACCEI, 2024)
The environment is negatively impacted by occasional discharges from industrial activity. When these events contain insoluble compounds such as fats and oils, they are high impact pollutants. This work focuses on an environmental problem in the industrial area of Buenos Aires, Argentina, where a lagoon was contaminated by vegetable oil residues. The aim of this work is to study bioremediation strategies in order to propose solutions for the remediation of the lagoon. For this way, autochthonous vegetable oil degrading bacteria were isolated from Lagoon 3, and the conditions to produce bacterial biomass were evaluated. Then, through microcosms systems using contaminated coastal soil, different site-specific treatments were tested: a control as natural attenuation a bioaugmentation treatment with autochthonous vegetable oil degrading bacteria two biostimulation treatments with nitrogen and phosphorus, and with depleted mushroom compost waste. Although both bioaugmentation and biostimulation showed promising results, biostimulation with N, P was the most effective for site-specific biorremedmediation of Lagoon 3, achieving 67 % of oil vegetable reduction at 60 days.